2021
DOI: 10.1108/jarhe-09-2020-0288
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of using blended learning teaching and learning strategy to develop students' performance at higher education

Abstract: PurposeThe research aims to identify the effectiveness of using the blended learning strategy on achievement among students of higher colleges of technology in the United Arab Emirates (UAE), through the answer to the following question: Is there a statistically significant difference at the significance level (a = 0.05) in students' achievements in general studies courses at higher education attributed to the method of teaching (blended learning, traditional).Design/methodology/approachThe research applied a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…Blended learning results in better academic outcomes for learners and increases engagement [ 6 , 36 ]. A blended learning approach facilitates equipping learners with skills to continue their education, helps them to self-diagnose their educational needs, and searches for appropriate educational resources while at the same time providing customization and flexibility in learning [10] . In the event of climate-related natural disasters or disruptive situations such as the COVID-19, blended learning allows the continuity of education [6] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blended learning results in better academic outcomes for learners and increases engagement [ 6 , 36 ]. A blended learning approach facilitates equipping learners with skills to continue their education, helps them to self-diagnose their educational needs, and searches for appropriate educational resources while at the same time providing customization and flexibility in learning [10] . In the event of climate-related natural disasters or disruptive situations such as the COVID-19, blended learning allows the continuity of education [6] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kang et al [27] verify a flipped classroom on knowledge, problem-solving, and satisfaction student in designing BL. Ayob et al [28] identify the effectiveness of using the strategy of BL toward higher students in the United Arab Emirates. Shantini et al [29] found several factors that influence the implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated a statistically significant difference between the mean scores in which the experimental group receiving blended learning delivery outperformed the control group in an achievement test. 15 Blended learning was adopted in this study because it increased learner acceptance, improved learner engagement and motivation, reduced training expenses, and reached more learners who may have some control over some aspects of their learning such as time, location, and path. It also boosts student retention and dedication to their educational goals.…”
Section: Introductionmentioning
confidence: 99%